Pemberdayaan Masyarakat Melalui Inovasi Produk Olahan: Pembuatan Tekwan Berbahan Dasar Ikan Tongkol Komo - Ridwan, Mutmainnah; Yuliana, Yuliana; Putri, Saptariana; Mukminati, Mukminati; Paembonan, Rustam E. (Jurnal Pengabdian Kepada Masyarakat Undana, 2025)
This community service program aims to increase the added value of ikan komo (bullet tuna, Euthynnus affinis), one of the abundant marine resources in Ternate City, through the innovation of a traditional culinary product—tekwan. The activity was carried out in Gambesi Village, where most residents work as fishermen and food-based micro-entrepreneurs. The methods involved nutrition education, economic potential analysis of ikan komo, training on tekwan processing using bullet tuna, and assistance with packaging and digital marketing strategies. The main result shows that the community successfully processed ikan komo into a well-received tekwan product, which has strong potential to be developed as a local food innovation. A new finding reveals that ikan komo has a high protein content and a suitable texture for tekwan production. In conclusion, this program enhanced community capacity in both economic and technical aspects while reinforcing local food identity. Its significance lies in integrating local fishery resources with sustainable and economically viable food product innovation.